Observaţii critice faţă de tratamentul sancţionator inechitabil admis de legiuitorul moldav în procesul incriminării unor fapte infracţionale: cazul art.329 din Codul penal [Articol] - Copețchi, Stanislav (CEP USM, 2019)
În prezentul studiu se punctează că sancţiunea normelor prevăzute la lit.a) şi b) alin.(2) art.329 CP RM conferă acestora neconstituţionalitate, fapt desprins din analiza comparativă a sancţiunii înscrise la alin.(2) art.329 CP RM în raport cu cea stipulată la alin.(2) art.327 CP RM. Mai exact, se observă că sancţiunea normelor consemnate la alin.(2) art.327 CP RM care, inter alia, stabileşte răspunderea penală pentru abuzul de putere sau abuzul de serviciu soldat cu urmări grave, este mai blândă ca sancţiunea normelor prevăzute la alin.(2) art.329 CP RM (neglijenţa în serviciu care a provocat decesul persoanei sau alte urmări grave), fapt ce contravine principiului stabilirii pedepselor reieşind din gradul de pericol social pe care îl comportă fapta prejudiciabilă şi persoana făptuitorului. Se demonstrează că o atare situaţie pare a fi discriminatorie, deoarece pune într-o lumină nefavorabilă persoanele învinuite de săvârşirea neglijenţei în serviciu care a provocat decesul persoanei sau alte urmări grave, în raport cu persoanele învinuite de săvârşirea abuzului de putere sau abuzului de serviciu soldat cu urmări grave.

In this study there it is pointed that the sanction of the norms stipulated in letters a) and b) paragraph 2) of art.329 PC RM gives them unconstitutionality, fact resulting from comparative analysis of the sanction stipulated in paragraph (2) of art.329 PC RM in relation to sanction stipulated in paragraph (2) of art.327 PC RM. More exactly, it is noted that the sanction of the norms stipulated in paragraph (2) of art.327 PC RM which, inter alia, establishes criminal liability for the abuse of power or abuse of official position that caused severe consequences is milder than the sanction of the norms stipulated in paragraph (2) of art.329 PC RM (negligent performance of duties that caused the death of a person or other severe consequences) which contradicts to the principle of establishing penalties based on the degree of social danger which represents the prejudicial act and the perpetrator. Is demonstrating that such situation seems to be discriminatory, because it puts in an unfavorable position persons accused of committing negligent performance of duties that caused the death of a person or other severe consequences in relation to persons accused of committing abuse of power or abuse of official position that caused severe consequences.
CRITICAL OBSERVATIONS REGARDING INEQUITABLE SANCTIONING TREATMENT ADMITED BY THE MOLDOVAN LEGISLATOR IN THE PROCESS OF INCRIMINATION SOME OFFENCES: THE CASE OF art.329 FROM THE PENAL CODE
Keywords: neglijenţă în serviciu; abuz de putere sau abuz de serviciu; egalitate; discriminare; negligent performance of duties; abuse of power or abuse of official position